2019
DOI: 10.5194/bg-16-4647-2019
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular fungal ice nuclei in <i>Fusarium</i>: effects of physical and chemical processing

Abstract: Abstract. Some biological particles and macromolecules are particularly efficient ice nuclei (IN), triggering ice formation at temperatures close to 0 ∘C. The impact of biological particles on cloud glaciation and the formation of precipitation is still poorly understood and constitutes a large gap in the scientific understanding of the interactions and coevolution of life and climate. Ice nucleation activity in fungi was first discovered in the cosmopolitan genus Fusarium, which is widespread in soil and plan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 92 publications
8
89
0
Order By: Relevance
“…Similarly, based on the measurements by Attard et al 2012, we derived values of 28°, 33°, and 44° for different types of bacteria. θ values for fungi based on the measurements by Kunert et al (2019) are similar (30°≤ θfungi ≤ 33°). Gute and Abbatt (2018) performed deposition freezing experiments of pollen; based on their experiments, we fitted θpollen = 15° for silver birch and θpollen = 16.3° for grey alder.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Similarly, based on the measurements by Attard et al 2012, we derived values of 28°, 33°, and 44° for different types of bacteria. θ values for fungi based on the measurements by Kunert et al (2019) are similar (30°≤ θfungi ≤ 33°). Gute and Abbatt (2018) performed deposition freezing experiments of pollen; based on their experiments, we fitted θpollen = 15° for silver birch and θpollen = 16.3° for grey alder.…”
mentioning
confidence: 71%
“…Based on these data, we calculated that the contact angle increased by ~1° after nitration for some bacteria. In contrast, Kunert et al (2019) reported 265 that protein nitration does not influence the cumulative fraction of IN for 65 species of fungi investigated.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Heterogeneous ice nucleation regarding biological organisms has been reported in plants (Diehl et al, 2001;Pummer et al, 2012), bacteria (Lindow et al, 1982;Wolber et al, 1986), fungi (Pouleur et al, 1992;Fröhlich-Nowoisky et al, 2015;Kunert et al, 2019;Iannone et al, 2011;Haga et al, 2013), moss spores (Weber, 2016), and lichen (Kieft, 1988). Plants growing in temperate environments use mechanisms such as extracellular freezing (Burke et al, 1976;Storey and Storey, 2005;Pearce, 2001) or extra-organ freezing (Quamme, 1978;Ishikawa and Sakai, 1981) to survive sub-zero temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…(Pummer et al, 2012;Diehl et al, 2001). Past studies showed that INPs from biological systems are rather in a macromolecular size range (ice-nucleating macromolecules, INM) (Pummer et al, 2012;Kunert et al, 2019). If those INMs can be easily washed off a plant's surface, they would have the potential to become aerosolized and serve as an important source for INPs in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%